PERBANDINGAN EFEKTIFITAS KOMBINASI TERAPI AROMA DAN MUSIK DENGAN KOMBINASI TERAPI AROMA DAN NAFAS DALAM UNTUK MENURUNKAN TEKANAN DARAH - Muhammad N., Aditya; Wahyuningsih, Melania; Natalia R., Listyana (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023, 2023)
High blood pressure is a disorder of the cardiovascular system. Nonpharmacological treatments are aimed at lowering blood pressure including a combination of lavender aromatherapy with music and a combination of lavender aromatherapy with deep breathing therapy. The purpose of this study was to compare the effectiveness of a combination of lavender aromatherapy and music therapy with a combination of lavender aromatherapy and breath therapy to reduce blood pressure. This type of quasi-experimental research with pre and posttest without control. The sample consisted of 34 hypertension sufferers. Sampling technique with convenience sampling. Data analysis using paired t test and independent t-test. The effectiveness of the combination of lavender aroma therapy with music therapy to reduce systolic blood pressure with p-value of 0,000 < 0,05 and in diastolic blood pressure with p-value of 0,000 <0,05. The effectiveness of combination of lavender aroma therapy and deep breathing therapy to reduce systolic blood pressure p-value 0,004 < 0,05 and diastolic blood pressure p-value 0,246 > 0,05. Comparison of the effectiveness before intervention of a combination of lavender aroma therapy and music therapy with a combination of lavender aroma therapy and deep breathing therapy to reduce systolic blood pressure p-value 0,622 > 0,05, diastolic blood pressure p-value 0,185 > 0,05. Comparison of the effectiveness after the intervention of a combination of lavender aroma therapy and music therapy with a combination of lavender aroma therapy and deep breathing therapy to reduce systolic blood pressure p-value 0,969 > 0,05 and diastolic blood pressure p-value 0,806 > 0,05. The combination of lavender aromatherapy and music therapy and the combination of lavender aromatherapy and breath therapy are effective in reducing systolic and diastolic blood pressure.